2019
DOI: 10.1177/0890117119835518
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Preconception Health Knowledge: A Systematic Review

Abstract: Objective: Preconception health is an important determinant of maternal, paternal, and infant outcomes. Knowledge is commonly used to evaluate the effectiveness of interventions to promote preconception health. Our objective was to examine how preconception health knowledge has been measured in the existing literature and to identify measurement gaps, biases, and logistical challenges. Data Source: MEDLINE, EMBASE, PsycINFO, CINAHL, the Cochrane Database of Systematic Reviews, and gray literature were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 68 publications
(361 reference statements)
0
23
0
Order By: Relevance
“…Development of the PHKQ was informed by a systematic review on preconception health knowledge tools. 9 The PHKQ adapted 8 items from the Locally Driven Collaborative Project Healthy Pregnancy Knowledge Survey, 15 which assessed pregnancy, lifestyle, and breastfeeding knowledge in women attending prenatal programs, and 2 items from a study by Coonrod et al , 16 which used a 15-item tool to evaluate knowledge on maternal age, family and genetic history, medication use, tobacco use, alcohol and substance use, infectious disease, immunization, psychosocial stressors, nutrition, physical activity, and environmental exposures. Based on consultation with 6 public health nurses, one health promotion specialist, and 2 family physicians, 15 items were added related to interconception health, men’s health, mental health, specific immunizations, and weight changes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of the PHKQ was informed by a systematic review on preconception health knowledge tools. 9 The PHKQ adapted 8 items from the Locally Driven Collaborative Project Healthy Pregnancy Knowledge Survey, 15 which assessed pregnancy, lifestyle, and breastfeeding knowledge in women attending prenatal programs, and 2 items from a study by Coonrod et al , 16 which used a 15-item tool to evaluate knowledge on maternal age, family and genetic history, medication use, tobacco use, alcohol and substance use, infectious disease, immunization, psychosocial stressors, nutrition, physical activity, and environmental exposures. Based on consultation with 6 public health nurses, one health promotion specialist, and 2 family physicians, 15 items were added related to interconception health, men’s health, mental health, specific immunizations, and weight changes.…”
Section: Methodsmentioning
confidence: 99%
“…One commonly used outcome for evaluating such efforts is preconception health knowledge. 9 While knowledge must be considered within the context of the social determinants of health and the systemic barriers that affect individuals’ abilities to act on their knowledge, Social Cognitive Theory and the Theoretical Domains Framework 10 -13 show that lack of knowledge is an obstacle to health behavior change. 14 Knowledge can be measured with simple, efficient, and cost-effective methods, making it a more accessible indicator of changes related to preconception health than long-term behavior change or incidence of rare outcomes such as congenital anomalies.…”
Section: Purposementioning
confidence: 99%
See 1 more Smart Citation
“…Sporadic efforts are made to provide information about preconception care. A systematic review revealed the tools used impart knowledge usually focus on fertility, folic acid supplementation, alcohol consumption, mental health and some questions about men's health [15]. In a study in the US, lack of knowledge was identified as the biggest barrier to the practice of preconception behaviour, the second most important barrier being the cost [16].…”
Section: Generalmentioning
confidence: 99%
“…Knowledge or awareness about PCC differs widely in different countries. A systematic review of 34 studies from 14 countries with data collected in 2000 to 2017 revealed the preconception health knowledge tools usually focus on fertility, folic acid supplementation, alcohol consumption, mental health and some issues about men's health [11,15,20,21]. Another systematic review of studies done during 1998 and 2008 focusing on factors related to preconception health behaviors among childbearing age women in the United States, developed countries, and developing countries identified six major thematic areas: frequency of alcohol intake prior and during pregnancy, glycemic control/diabetes management, physical activity before and during pregnancy, pregnancy planning behavior, cystic fibrosis carrier screening, and other risk factors [22].…”
Section: Preconception Services: Knowledge and Utilizationmentioning
confidence: 99%